Saving Stalin's imperial city : historic preservation in Leningrad, 1930-1950 - Maddox, Steven, 1979- (Indiana University Press, 2015)
"Saving Stalin's Imperial City is a story of preservation, restoration, and commemoration in Leningrad during and after World War II. It is a history of the successes and failures in historic preservation and of Leningraders' determination to preserve the memory of the terrible siege the city had survived. The book stresses the counterintuitive nature of Stalinist policies, which allocated scarce wartime resources to save historic monuments from the tsarist and imperial past when the very existence of the Soviet state was threatened, and again after the war, when housing, hospitals, and schools needed to be rebuilt. While not all monuments were safe from destruction, the state's ideological move toward promoting Soviet patriotism led to policies that promoted heritage preservation, especially after Germany systematically sought to destroy monuments as a means of erasing evidence of Russian history and culture. When the war ended, Leningrad was at the forefront of a concerted restoration effort, fueled by commemorations that glorified the city's wartime experience, encouraged civic pride, and mobilized residents to restore their hometown. For Leningrad, the restoration of monuments and commemorations of the siege were intimately intertwined, served similar purposes, and were mutually reinforcing"--Provided by publisher.